History of the Department of Dermatology in Gdansk. The profiles of heads of the Department from the post-war period to modern times - Purzycka-Bohdan, Dorota; Szczerkowska-Dobosz, Aneta; Nowicki, Roman; Wilkowska, Aleksandra (Dermatology Review/Przegląd Dermatologiczny, 2014)
With respect to the achievements of contemporary medicine, it is vital to remember the history and physicians who created structures and aimed at developing many branches of medicine. The history of the Dermatology Department in Gdansk – one of the oldest clinics in the Medical University of Gdansk – and biographies of its professors were recalled during many anniversaries and jubilees as a sign of respect to the founders and continuators of the School of Dermatology in Gdansk. Without their hard work and devotion, the progress in diagnosis and treatment of many dermatological diseases would not be seen. In the post-war period the Department of Dermatology in Gdansk was famous for its success in elimination of an epidemic of venereal diseases. The following years were difficult due to reorganization of the health service in Poland and opening of new diagnostic laboratories which are necessary for contemporary dermatology. Apart from its therapeutic function, the department conducts scientific research and medical training which results in many publications, international cooperation, organization of conferences and education of qualified medical staff. The forthcoming 70 th anniversary of the foundation of the Dermatology Department in Gdansk is an excellent opportunity to recall and to present profiles of the professors who were the heads of the department from the post-war period to modern times: Prof. Tadeusz Pawlas, Franciszek Miedzinski, Jerzy Kozakiewicz, Henryk Szarmach and Prof. Jadwiga Roszkiewicz.